Immune cell regulatory networks in chronic obstructive pulmonary disease: mechanistic analysis from innate to adaptive immunity - Li, Hui; Wang, Yingqi; Duan, Hongxia; Bao, Yidie; Deng, Xinliao; He, Yucheng; Gao, Qian; Li, Peijun; Liu, Xiaodan (Frontiers in Immunology, 2025)
BackgroundChronic Obstructive Pulmonary Disease (COPD) is a leading cause of global mortality, characterized by chronic inflammation and abnormal immune responses in the lower airways. Recent studies have highlighted the critical role of immune function in the pathogenesis and progression of COPD. The disease is characterized by abnormal immune responses in the lower respiratory tract, with its progression associated with the infiltration of innate and adaptive inflammatory immune cells into the lungs and the formation of lymphoid follicles, mediated by cytokines and inflammasomes. Increasing evidence suggests that cell-mediated immunity has an important role in the pathogenesis of COPD, which is characterized by immune senescence leading to decreased resistance to infection, enhanced neutrophil and macrophage activation, T-cell infiltration, and aberrant B-cell activity, all of which combine to contribute to airway inflammation and lung injury in patients with COPD.ObjectiveThis review aimed to explore the pivotal role of the immune system in COPD and its therapeutic potential.MethodsWe reviewed, categorized, and summarized literature on immunity and COPD published in the last five years from Web of Science and PubMed databases.ResultsThis study elucidates the pivotal role of immune dysregulation in COPD pathogenesis, particularly the dysfunctional transition from innate to adaptive immunity. We delineate how specific immune cell populations—including macrophages, neutrophils, and T-lymphocytes—contribute to sustained airway inflammation and lung injury in COPD through aberrant activation, infiltration, and impaired function. Mechanistically, key features of this dysregulation involve aberrant cytokine signaling pathways and defective resolution of inflammation. These insights reveal potential therapeutic targets for immunomodulatory strategies aimed at interrupting the chronic inflammatory cascade, restoring immune homeostasis, and mitigating infection susceptibility in COPD. Promising approaches highlighted include targeting specific cytokines, modulating macrophage polarization states, and enhancing mucosal immune defenses.